2021
DOI: 10.1093/qjmed/hcab024
|View full text |Cite
|
Sign up to set email alerts
|

The value of telephone consultations during COVID-19 pandemic. An observational study

Abstract: Background many Spanish hospitals converted scheduled in-person visits to telephone visits during the COVID-19 lockdown. There is scarce information about the performance of those visits. Aim to compare telephone visits during the COVID-19 lockdown period with previous in-person visits Design retrospective descriptive study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
(10 reference statements)
1
11
0
Order By: Relevance
“…The tool suggested in this work can be applied in different scenarios of pharmaceutical care. Among possibilities of pharmacist teleconsultation's applications, we can mention the identi cation of inappropriate medication use [20], ADR identi cation [4], [20], [21], the detection of drug-related problems [4], [20], and improved adherence [4]; often with positive feedbacks from patients and professionals about the telemedicine use [12], including phone calls [22].…”
Section: Discussionmentioning
confidence: 99%
“…The tool suggested in this work can be applied in different scenarios of pharmaceutical care. Among possibilities of pharmacist teleconsultation's applications, we can mention the identi cation of inappropriate medication use [20], ADR identi cation [4], [20], [21], the detection of drug-related problems [4], [20], and improved adherence [4]; often with positive feedbacks from patients and professionals about the telemedicine use [12], including phone calls [22].…”
Section: Discussionmentioning
confidence: 99%
“…The study further depicts that 12.0% of adults also avoided urgently or emergency care, and just under a third of adults (31.5%) avoided routine care. A study comparing health facility visits from March to May 2020 with in-person visits during the same period in 2019, the results showed a reduction of 52% and 47% of emergency department visits and hospital admissions was observed compared to in-person visits (p < 0.01) [3]. The study also found that, of 120 patients surveyed, 95% were satisfied/very satisfied with the telephone visits.…”
Section: Introductionmentioning
confidence: 91%
“…According to authors such as Martos-Pérez et al and Downes et al, telephone consultations could ease up the overburdened healthcare system [3][4][5]. A study by Bokolo found that telemedicine and virtual software as one of the contributing factors to the decrease in the number of visits to emergency rooms [6].…”
Section: Virtual Consultations During Emergenciesmentioning
confidence: 99%
See 2 more Smart Citations